Analysis of Legislation and Regulations on the Fulfillment of Restitution Rights for Sexual Violence Victims in Indonesia - Lilis; Muslim, Ikhwanul (Universitas Ahmad Dahlan, 2025)
Sexual violence considers as criminal acts that harm the victim tremendously, in line with that Indonesian government regulates the granting of rights in several legislative provisions for the victims, one form of which is restitution. However, restitution has not been effectively implemented, as evidenced by several court decisions that have not yet included restitution for victims of sexual violence. Therefore, the purpose of this research is to determine how legislative provisions regulate the mechanism for granting restitution and to find a legislative provision that can provide certainty for the fulfillment of restitution rights for victims of sexual violence. The research method used in this study is normative, with a legislative approach that is then analyzed by describing the data that has been obtained. The data collection technique used in this study is to analyze the articles in the legislative provisions regarding restitution. The results of this study indicate that the most ideal legislative provision to grant restitution rights to victims of sexual violence is Law Number 12 of 2022 concerning Sexual Violence, in which this provision provides certainty and overall justice to victims in obtaining their restitution rights.